Kim - Kipling, Rudyard (Ware, Hertfordshire Wordsworth Classics, 1993)
An exciting and touching tale of an Irish orphan-boy who has lived free in the streets of Lahore before setting out, with a Tibetan Lama, on a double quest. This eventually leads to enrollment in the Indian Secret Service and a thrilling climax in the Himalayas.
This novel tells the story of Kimball O' Hara (Kim), who is the orphaned son of a soldier in the Irish regiment stationed in India during the British Raj. It describes Kim's life and adventures from street vagabond, to his adoption by his father's regiment and recruitment into espionage.
Keywords: India -- Orphans